Identificação e manejo da mosca-minadora (Liriomyza sp.) na culltura do maracujazeiro - Vitoria, Rafael Zucateli da (2019)
The passionfruit (Passiflora edulis f. flavicarpa Deg.) is a plant native to Brazil, which is the largest of the global fruit production. Among the states of the federation, Espírito Santo was the sixth largest producer in 2017. The passion fruit crop has been suffering from pest attacks and most often to the point of negatively influencing its agronomic performance. The presence of leaf miner in crops has been causing damage, which has been increasing every year due to the lack of information, from identification to efficient control methods of this insect pest. Based on the above, the objective of this work was to identify the species of mining fly, to determine the method of spraying and dose of Cartap Hydrochloride to control it. A survey was conducted in five commercial crops. Then, the droplet spectrum characterization of the tips BX-AP/90 and MAG CH 5 was performed in laboratory and field with three spray rates 600, 700 and 800 L ha-1. For the applied control, the insecticide cartap hydrochloride was used in five different doses 30, 45, 60, 75 and 90 mg i.a. and one control. It was found that this is a pest of the genus Liriomyza, this being the first record of Liriomyza sp. in passion fruit. The diameter of the droplets produced by the tips BX AP/90 e MAG CH 5 dacreases with increasing working pressure. The spray tip BX AP/90 presented better performance when compared to the MAG CH 5. The volume of 600 L ha-1 it is more efficient among the others, when the tip BX-AP/90. The cartape hydrochloride has medium efficacy in the control of Liriomyza sp. The higher the dose of cartape hydrochloride the longer the survival time and the higher the mortality rate of larvae of Liriomyza sp. The letal dose of cartape hydrochloride to control 50% of the population of Liriomyza sp. in passion fruit was 81.97 mg i.a.